1988
DOI: 10.1093/eurheartj/9.suppl_a.63
|View full text |Cite
|
Sign up to set email alerts
|

When does nitrate tolerance develop? What dosages and which intervals are necessary to ensure maintained effectiveness?

Abstract: To address the issues of tolerance development and its circumvention during long-term treatment with nitrates, several controlled studies have been performed. In patients with coronary artery disease, during long-term treatment with isosorbide dinitrate (ISDN) in sustained-release form at dosages of 20 mg t.i.d., 40 mg t.i.d. and 60 mg t.i.d., both the rate of anginal attacks and the ischaemic reaction to exercise were unaffected. After a marked acute anti-ischaemic effect to 40 mg ISDN in nonsustained-release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…Nitrates have been shown to induce immediate tolerance in previous studies conducted in vivo and in vitro [8,9,19,28], although the mechanism of tolerance induction through nitrate administration has been unclear until the present time. However, it has been demonstrated that the intermittent administration of nitrates with a drug-free time of 10 to 12 hours can prevent development of tolerance [10,24].…”
Section: Discussionmentioning
confidence: 90%
“…Nitrates have been shown to induce immediate tolerance in previous studies conducted in vivo and in vitro [8,9,19,28], although the mechanism of tolerance induction through nitrate administration has been unclear until the present time. However, it has been demonstrated that the intermittent administration of nitrates with a drug-free time of 10 to 12 hours can prevent development of tolerance [10,24].…”
Section: Discussionmentioning
confidence: 90%
“…Since nitrates are generally used to improve angina pectoris with resultant-induced tolerance, studies on nitrate have focused on its acute effects [13,28]. Nitrates have been shown to induce immediate tolerance in previous in vivo and in vitro studies [12,34]. Whereas the mechanism that induces tolerance through nitrate administration was unclear until recently [14,16], setting a drug-free time of 10 to 12 hr has been shown to prevent tolerance development [7,11,29].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrates have been used for more than 100 years in the treatment of angina pectoris [2,19], ischemic heart disease, and chronic heart failure [8,9,24,30]. Unfortunately, the use of nitrates has the disadvantage of inducing tolerance when administered for long periods [12,13,22,34]. The effect of prolonged use of nitrates on the prognosis for survival and prophylaxis of future cardiac events remains unclear [26].…”
mentioning
confidence: 99%
“…In the recent decades the expanding knowledge on the pharmacodynamic and pharmacokinetic properties of nitrates al lowed new therapeutic approaches to long term treatment of coronary artery disease and heart failure [1,6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous administration of nitrates, regardless of the formulation, results in at tenuation of their hemodynamic and antiischemic effects [9], This tolerance can be avoided by interval (intermittent) adminis tration [12][13][14], High doses of slow-releasc IS-5-MN, once daily in the morning, result in therapeutic plasma levels for 12-15 h with lowering during the night, which is sufficient to prevent tolerance [9,[15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%